2013
DOI: 10.12688/f1000research.2-96.v1
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Drug Delivery (ITDD) systems for cancer pain

Abstract: Intrathecal drug delivery is an effective pain management option for patients with chronic and cancer pain. The delivery of drugs into the intrathecal space provides superior analgesia with smaller doses of analgesics to minimize side effects while significantly improving quality of life. This article aims to provide a general overview of the use of intrathecal drug delivery to manage pain, dosing recommendations, potential risks and complications, and growing trends in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 9 publications
2
53
0
Order By: Relevance
“…The initial IT morphine dose was calculated from the baseline opioid use with an oral–IT morphine conversion ratio of 300:1. [11] The initial infusion was started at a flow rate of 0.1 mL/h without PCIA dose for safety reasons. IT morphine titration was conducted 1 day after the procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial IT morphine dose was calculated from the baseline opioid use with an oral–IT morphine conversion ratio of 300:1. [11] The initial infusion was started at a flow rate of 0.1 mL/h without PCIA dose for safety reasons. IT morphine titration was conducted 1 day after the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Opioid use was calculated by morphine oral equivalent dose. [11] Systemic opioid use consisted of controlled-release opioid use (basal dose) and immediate-release as-needed opioid use (breakthrough dose). IT opioid use included continuous infusion morphine use (basal dose) and PCIA morphine use (PCIA dose).…”
Section: Methodsmentioning
confidence: 99%
“…This use of high concentrations in human pumps has led to local toxicity. For opiates, the manifestation of this toxicity is the intrathecal granuloma [37, 116, 461-463]. Our group showed that the primary determinant for intrathecal opiate granulomas is the local concentration to which the tissue adjacent to the catheter tip is exposed [49, 51, 52].…”
Section: Current Spinal Agentsmentioning
confidence: 99%
“…Intrathecal drug therapy is often effective for patients with chronic and cancer pain. By delivering the drugs via an intrathecal route, the risk of side effects of analgesics may be significantly decreased due to the substantially smaller doses required when compared to drugs given systemically . However, there is a risk of inadvertently administering too large doses intrathecally.…”
Section: Anesthetic Agents and Pain Medicationsmentioning
confidence: 99%